PENGARUH PENGGUNAAN HANDOUT BERORIENTASI PEMBELAJARAN TERPADU TIPE INTEGRATED TERHADAP PENCAPAIAN KOMPETENSI IPA PESERTA DIDIK KELAS VII SMPN 31 PADANG - Albinuz Deka Indra; Festiyed Festiyed; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2016)
One cause of low achievement IPA competence of learners is the lack of use of teaching materials with the essence of integrity of the material in accordance with the demands of the curriculum. As an alternative solution to overcome these problems is needed teaching materials that includes the integration of materials with integrated learning oriented. The purpose of this study to investigate the effect of the use of teaching materials handout integrated learning oriented towards achievement of competencies type of integrated science class VII students of SMPN 31 Padang. This type of research design Quasi Experiment with Randomized Control Group Only Design. This study population of students of class VII SMPN 31 Padang enrolled in the second semester of the school year of 2015/2016 with a random cluster sampling technique. In this study, the competence of the attitude measured using observation sheets, competency knowledge using written tests and competency skills are measured using a portfolio assessment. Based on research activities that have been implemented, the data obtained attainment of learners on three competence. The average value of achievement of competence attitudes and competence skills of the experimental class is bigger than the control class, where the average value in the attainment of knowledge of the control class higher than the experimental class. The results of data analysis research conducted at the level of 95% was concluded that there was no effect of the use of integrated learning handout oriented towards achievement of competencies type of integrated science class VII students of SMPN 31 Padang